2021
DOI: 10.1101/2021.07.05.21260017
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Public opinion on a mandatory COVID-19 vaccination policy in France: a cross sectional survey

Abstract: Introduction: In France, in June 2021, the daily number of first doses of COVID-19 vaccines is decreasing and vaccine coverage might be insufficient to achieve herd immunity. Making vaccination mandatory might contribute to increasing vaccine coverage although this measure could induce reactance. Our aim was to evaluate attitudes to mandatory COVID-19 vaccination in France. Our aim was to evaluate attitudes of toward COVID-19 mandatory vaccination in France. Methods: Between the 10th and the 23rd of May 2021,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Then, hierarchical regression models investigated whether the four ideologies predicted support for vaccine mandates and the punishment of unvaccinated individuals, with or without the inclusion of COVID-19 concern and vaccine acceptance. In prior research, these two factors are associated with ideological variables such as SDO, RWA, and libertarianism ( Bilewicz & Soral, 2021 ; Choma et al, 2021 ; Clarke et al, 2021 ; Murphy et al, 2021 ; Peng, 2022 ) as well as support for vaccine mandates ( Gagneux-Brunon et al, 2021 ). An inspection of the predicted probability plots and the residuals vs. predictor plots suggested that the assumptions for regression analyses were not violated.…”
Section: Resultsmentioning
confidence: 99%
“…Then, hierarchical regression models investigated whether the four ideologies predicted support for vaccine mandates and the punishment of unvaccinated individuals, with or without the inclusion of COVID-19 concern and vaccine acceptance. In prior research, these two factors are associated with ideological variables such as SDO, RWA, and libertarianism ( Bilewicz & Soral, 2021 ; Choma et al, 2021 ; Clarke et al, 2021 ; Murphy et al, 2021 ; Peng, 2022 ) as well as support for vaccine mandates ( Gagneux-Brunon et al, 2021 ). An inspection of the predicted probability plots and the residuals vs. predictor plots suggested that the assumptions for regression analyses were not violated.…”
Section: Resultsmentioning
confidence: 99%
“…The survey was conducted from 2 to 17 December 2021 as part of the SLAVACO research project [ 27 ]. SLAVACO is a multi-aim cross-sectional study.…”
Section: Methodsmentioning
confidence: 99%
“…There was no evidence of an association between the perception of this policy and the political orientation of the respondents. In a cross-sectional online survey among a representative sample of the French population conducted in May 2021, 43% of the respondents were in favor of mandatory COVID-19 vaccination, 41.9% were opposed to such a policy, and 15.1% were undecided [29]. The age groups of 18-24 and 25-34 years were significantly more opposed than the group of 75 years or older.…”
Section: Discussionmentioning
confidence: 98%